Transforming Self-Esteem in Indonesian Teens by Overcoming Body Shaming: Mengubah Harga Diri Remaja Indonesia dengan Mengatasi Body Shaming - Ula, Bella Mas; Azizah, Nurul (Universitas Muhammadiyah Sidoarjo, 2024)
Body shaming during adolescence, a critical period of self-identity formation, can severely impact self-confidence and mental well-being. This study examines the psychological effects of body shaming on SH, a 14-year-old student, and the effectiveness of targeted interventions. SH experienced significant sadness and social withdrawal due to negative comments about her weight gain during puberty. Interventions included counseling, education on puberty-related changes, a balanced diet, and regular exercise. Follow-up results showed SH's improved self-confidence and mental state. This study highlights the importance of comprehensive support to help adolescents cope with body shaming. Highlights: Impact on Self-Confidence: Body shaming during adolescence can lead to significant social withdrawal and loss of self-esteem. Effective Interventions: Counseling, proper diet, and regular exercise can help mitigate the negative psychological effects. Positive Outcomes: Targeted interventions resulted in improved self-confidence and mental well-being for the affected individual. Keywords: Body Shaming, Adolescence, Self-Confidence, Psychological Impact, Intervention